Strawberry plants regenerated in vitro by direct organogenesis at different concentrations of auxins and cytokinins (Bioagro, 2025)
The strawberry (Fragaria x ananassa) is a plant species of great economic and agri-food importance, which is grown in agro-industrial regions of Mexico such as Bajío. The main input for agricultural production is seedlings, whose first stage of multiplication begins with the formation of clones by in vitro culture from selected mother plants. However, several characteristics of the regenerated plants may present variations that reduce their agronomic and commercial value. This variability is due to multiple factors, although the effect of auxin and cytokinin combinations, as well as their concentrations, stands out. The aim of the present study was to regenerate strawberry plants in vitro by direct organogenesis at different concentrations of auxins and cytokinins. Explants were obtained from apical meristems on the stolons of mother plants of the Camino Real variety. A total of 21 treatments of auxins (indole-3-butyric acid –IBA and 2,4-dichlorophenoxyacetic acid –2,4-D) and citocinins (benzylaminopurine –BAP and kinetin) were used for organogenesis evaluation. The highest number of vitro plants regenerated with the combination of IBA and BAP at 0,4 mg·L-1, with an average regeneration rate of 68,3 %. In this treatment, the vitro plants showed better development and high antioxidant response. The highest average proline concentration of 1,7 µg mL-1, in the control treatment without auxins or cytokinins.
Keywords: Cloning; Fragaria x ananassa; in vitro culture; vitroplants